The Use of Facebook by Investors - Peter Garlans Sina (Jurnal Economia, 2016)
Abstract:  The Use of Facebook by Investors. The purpose of this study is to give additional evidence of the negative impacts of the use of Facebook as a social networking between investors in making investment decisions and how to reduce it. The results showed that the use of Facebook leads to the formation of erroneous beliefs that tend to make bias investment decisions. At the end of the study, it was described how to reduce them.Keywords: investment, social network, facebookAbstrak:  Penggunaan Facebook oleh Investor. Tujuan dari penelitian ini adalah memberikan bukti tambahan tentang dampak negatif dari penggunaan facebook sebagai jejaring sosial antara investor dalam membuat keputusan investasi serta bagaimana cara mereduksinya. Hasil menunjukkan bahwa penggunaan facebook mengarahkan pada pembentukan keyakinan yang keliru sehingga bertendensi membuat keputusan investasi yang bias. Pada bagian akhir penelitian ini, dijabarkan cara mereduksinya. Kata-Kata Kunci: investasi, jaringan sosial, facebook